Dynamic dependence nexus and causality of the renewable energy stock markets on the fossil energy markets. (15th October 2021) - Jiang, Yonghong; Wang, Jieru; Lie, Jiayi; Mo, Bin
Abstract: This study examines the impact of the renewable energy stock markets on the fossil energy markets (oil, coal and gas) with the quantile-on-quantile (QQ) and causality-in-quantiles (QC) approaches. The main empirical results from the QQ approach present the general positive dependence with varying degrees concerning different types of fossil energy and across various quantiles. Their dependence is relatively strong when the oil and coal markets are bullish and bearish, but appears to be weak or insignificant in the gas market. According to the nonparametric QC approach, the causality in variance is generally more evident than the causality in mean. Similarly, the causality varies across quantiles in the cases of different fossil energy. There is evidence of first and second order causality from the renewable energy stock markets to oil and coal markets in some of their quantiles, but the result is insignificant for the gas market. Highlights: We examine the impact of renewable energy stock markets on fossil energy markets. The dependence and causality vary with market conditions represented by quantiles. The quantile-on-quantile analysis indicates the positive dependence in general. Causality-in-variance is generally more significant than causality-in-mean. Among three fossil energy markets, the relationships are the weakest regarding gas.